OPTIMALISASI PELAYANAN PUBLIK MENINGKATKAN KEPERCAYAAN MASYARAKAT MELALUI RELIABILITY DAN RESPONSIVENESS (STUDI KASUS PELAYANAN KANTOR DESA TANJUNG HARAPAN KECAMATAN ALALAK KABUPATEN BARITO KUALA) - Dewi Merdayanty; Setiawati, Budi; Iswiyati Rahayu; Winda Emelia; Nida Pratiwi Armidina; Muhammad Riyandi Firdaus (stiatabalong.ac.id, 2025)
Tanjung Harapan Village has potential can be optimized in the form of fertole rice fields, clean river water, swallow farms, and friendly people, but this village bid challenges in the form of badly damaged road infrastructure, so it need attention from public service from the Village Government. Road construction really supports increasing public confidence through community welfare so as not to endanger road users and tranportation of agricultural products in village communities. The porpuse of research is to determine the optimization of public service to increase public trust through reliability and responsiveness at the Tanjung Harapan Village office, Alalak District, Barito Kuala Regency, because village roads in this area are badly damaged and need attention from the local government. This research is also to determine the factors that influence public services to increase reliability and responsiveness at the Tanjung Harapan Village office, Alalak District, Barito Kuala Regency. The research method uses qualitative methods and qualitative descriptive research, while data collection techniques use observation, interviews, documentation an triangulation. The informants for this research werw 4 people, namely the Village Head as key informant and the other informant were Head of the Village Government Section, the Head of the Community Welfare Section and 1 person from the village community. The data analysis technique uses interactive analysis starting from data collection, data reduction, data presentation, drawing conclusion an verification. The research results show that village office public service can increase public trust through reliability and responsiveness. Factors that influence the reliability and responsiveness of Tanjung Harapan village services include the availability of resources, competency of village officials, slow support from local government, coordination anf community participation. Keywords : Village Government; Reliability; Responsiveness